Dialectal Variation of Bugis Language in the Speech of Makassar State University Students to Fellow Bugis Speakers - Khaerunnisa, Khaerunnisa; Fiddienika, Arief; Perdana, Dyah Adila (Universitas Nusantara PGRI Kediri, 2025)
This research aims to identify and describe the variations of the Bugis dialect in the speech of students at Makassar State University (UNM) towards fellow Bugis speakers, as well as to analyze the social factors that influence the use of these dialects. The issue raised stems from the phenomenon of the diversity of Bugis language forms used by students from various regions in South Sulawesi, such as Sidrap, Wajo, Soppeng, Bone, and Sinjai, in daily interactions on campus. This study uses a descriptive qualitative approach with data collection methods in the form of participatory observation and in-depth interviews with ten native Bugis language speakers. The research results show a striking lexical and phonological variation, both in vocabulary selection and pronunciation. Factors such as regional origin, closeness of social relationships, and formal or informal contexts also influence the choice of dialect used. The findings also indicate the presence of linguistic accommodation strategies, where speakers adjust their dialects to build effective and inclusive communication. This research emphasizes that dialectal variations not only reflect the richness of local linguistics but also serve as symbols of identity and social solidarity in a multicultural campus environment.